2022
DOI: 10.1002/hec.4574
|View full text |Cite
|
Sign up to set email alerts
|

Does weight impact adolescent mental health? Evidence from China

Abstract: In this paper, we examine the causal impact of weight on adolescent mental health. Using the China Family Panel Studies, we find significant negative effects of adolescent weight, instrumented by cohort‐level parental body mass index (BMI), on mental illness. In particular, a one standard deviation increase in adolescent BMI z‐score decreases the K6 score by 0.766 (or 0.232 standard deviations). This finding is contrary to recent evidence from adults. We find this contrast can partly be explained by the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…The CFPS database tracks and collects information at the individual, household, and community levels, covering a wide range of research topics, including economic activities, family relationships and dynamics, population migration, and health. These data have been widely used in health research ( 45 , 46 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFPS database tracks and collects information at the individual, household, and community levels, covering a wide range of research topics, including economic activities, family relationships and dynamics, population migration, and health. These data have been widely used in health research ( 45 , 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies ( 28 , 46 ), we controlled for variables that may affect adolescent health, including individual, behavioral, family, and provincial dummy variables. Individual variables included age, gender(male/female, as assigned at birth), ethnicity, residence, academic stage, and whether they were in a single-parent family.…”
Section: Methodsmentioning
confidence: 99%
“…The literature shows complex associations between body mass index (BMI) and mental health . Studies in South Korea, eastern London, and the US observed a U-shaped BMI–mental health association .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in South Korea, eastern London, and the US observed a U-shaped BMI–mental health association . However, these studies often focus on single countries or short periods, limiting a comprehensive analysis across multiple countries and over time. Examining data from various countries and over extended periods allows for a better understanding of these trends in different cultural contexts and the influence of societal changes on the association between BMI and mental health.…”
Section: Introductionmentioning
confidence: 99%